South Africa 2010: Economic scope and limits - Swantje Allmers; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
This contribution provides an ex post analysis of the economic impacts of the two most recent single-country World Cups (WCs), Germany 2006 and France 1998. Based on macroeconomic indicators, the experiences of these WCs appear to be in line with existing empirical research on large sporting events and sports stadiums, which have rarely identified significant net economic benefits. Of more significance are the novelty effects of the stadiums, and 'intangible effects' such as the image effect for the host nations and the feel-good effect for the population. The experiences of former WCs provide a context for analysing the scope and limits for South Africa 2010. Like previous host countries, South Africa might have to cope with difficulties such as the underuse of most WC-stadiums in the aftermath of the tournament. On the other hand, this paper examines a handful of arguments why South Africa might realise larger economic benefits than former hosts of WCs, such as the absence of the northern-style 'couch potato effect' and the absence of negative crowding-out effects on regular tourism. Furthermore, the relative scarcity of sport arenas in South Africa might induce a larger positive effect than in countries with ample provision of sports facilities. In addition, against the backdrop of continuous declines in South African poverty since 2001, the novelty effect of new stadiums might be of special importance. Finally, the innovative South African ambitions to use stadiums with 'signature architecture' as a tool for urban development or to generate external effects for the regional economy are different from former WCs.
Keywords: L83; R53; R58; 330; Regional Economics; Sports Economics; World Cup; Stadium Impact; Feelgood Factor